The Effect Of Service Excellence On Customer Satisfaction - Thaher, Oday; , Ihwan Susila, SE., M.Si., Ph.D (2017)
This study was aimed to investigate in banking industries, the impact of service on customer's satisfaction. Sservice is as an attempt to serve the needs of others. Service eexcellence is an effort from organizations or company that more than expected, that focus on accuracy, safety, comfort, quality, cost, process, and satisfaction. The purpose of this study is to analyze the effect of service excellence on customer satisfaction. To collect the data and analyze the research question, Sample of 100 respondents of bank customer in Surakarta based on structured questionnaire and the method of 5 point Likert scale has been used to rate respondents feeling. The finding showed that there is positive and significant impact speed service, leisure service, hospitality service, and truth services on customer satisfaction.